2018
DOI: 10.1016/j.virol.2018.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Molecular dissection of distinct symptoms induced by tomato chlorosis virus and tomato yellow leaf curl virus based on comparative transcriptome analysis

Abstract: The viral infection of plants may cause various physiological symptoms associated with the reprogramming of plant gene expression. However, the molecular mechanisms and associated genes underlying disease symptom development in plants infected with viruses are largely unknown. In this study, we employed RNA sequencing for in-depth molecular characterization of the transcriptional changes associated with the development of distinct symptoms induced by tomato chlorosis virus (ToCV) and tomato yellow leaf curl vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
41
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 89 publications
0
41
0
Order By: Relevance
“…Simultaneous treatment with SA and TYLCV, both endogenous and exogenous SA induce the expression of SlPR1 , which increases the resistance of plant and reduces the accumulation of virus. Tomato plants infected with TYLCV virus will take a certain time to present the symptom phenotype [32, 43]. It was found that the leaf curl symptoms induced by TYLCV may be associated with the extreme down-regulation of the cellulose synthase family gene to decrease cellulose level [43].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Simultaneous treatment with SA and TYLCV, both endogenous and exogenous SA induce the expression of SlPR1 , which increases the resistance of plant and reduces the accumulation of virus. Tomato plants infected with TYLCV virus will take a certain time to present the symptom phenotype [32, 43]. It was found that the leaf curl symptoms induced by TYLCV may be associated with the extreme down-regulation of the cellulose synthase family gene to decrease cellulose level [43].…”
Section: Discussionmentioning
confidence: 99%
“…Tomato plants infected with TYLCV virus will take a certain time to present the symptom phenotype [32, 43]. It was found that the leaf curl symptoms induced by TYLCV may be associated with the extreme down-regulation of the cellulose synthase family gene to decrease cellulose level [43]. Appropriate SA concentration could increase the cellulose content in rice [44].…”
Section: Discussionmentioning
confidence: 99%
“…Chlorosis, yellowing, leaf size reduction, malformation or senescence are ‘general’ symptoms caused by several plant viruses. These changes usually coincide with alterations in photosynthetic activity or molecular structure of the host chloroplast [3439], but insights into molecular changes are still elusive.…”
Section: Resultsmentioning
confidence: 99%
“…With tomato yellow leaf curl virus, infected S . lycopersicum plants, especially when co-infected with tomato chlorosis virus, stunting was directly correlated to CESA8 down- and CWINV2 upregulation [34]. Investigation of the DEPs in N .…”
Section: Resultsmentioning
confidence: 99%
“…Some of the key research issues on which emphasis should be placed are listed below: The real molecular and biological diversity of ToCV should be revealed by sequencing and generation of infectious clones of isolates from plant hosts other than tomato. The molecular mechanisms underlying symptom development in plants infected by ToCV, an issue only barely studied (e.g. Seo et al , ), should receive further attention in order to understand how the disease initiates and progresses in the plant after horizontal transmission by whiteflies. Almost nothing is known about the molecular determinants of whitefly transmissibility of ToCV, especially on the insect side, and this can be extended to other criniviruses and semipersistently transmitted plant viruses in general. Identification of virus receptors in the whitefly will be a key step to clarify the mechanism of transmission and to design strategies to disrupt disease spread. Establishing correlations between climatic variables and distribution of whiteflies of the B. tabaci complex [especially those shown to efficiently transmit ToCV: MED (formerly Q biotype), MEAM1 (formerly B biotype) and NW (formerly A biotype)], T. vaporariorum and T. abutilonea will help to predict areas where ToCV is likely to emerge.…”
Section: Conclusion and Prospectsmentioning
confidence: 99%